Review of the genera Agelosus Sharp, 1889, Apostenolinus Bernhauer, 1934 and Apecholinus Bernhauer, 1933 (Coleoptera: Staphylinidae: Staphylinini: Staphylinina) - Smetana, Aleš (Zootaxa, 2018)
A taxonomic review of the genera Agelosus Sharp, 1889, Apostenolinus Bernhauer, 1934 and Apecholinus Bernhauer, 1933 is presented, including taxonomic history of the genera, their descriptions and keys to the species where applicable. Each species is described and illustrated, and all available bionomic and distributional data are presented. Agelosus caerulescens sp.n. (Yunnan), A. distigma sp.n. (China: Zhejiang), A. haeckeli sp.n. (Nepal), A. longicornis sp.n. (Japan: Shikoku), A. nigricollis sp.n. (China: Beijing Municipality, Hubei, Sichuan; North Korea), and A. schillhammeri sp.n. (China: Hubei) are described as new. Xanthocypus J. Müller, 1925 is removed from synonymy with Ocypus Leach, 1819 and moved as a resurrected synonym to Agelosus Sharp, 1889 (stat.res.) Ocypus fraternus Fairmaire, 1891, Agelosus ohkurai Hayashi, 1973, Ocypus aglaosemanticus He & Zhou, 2017, Ocypus liui He & Zhou, 2017 and Ocypus pterosemanticus He & Zhou, 2017 are transferred from Agelosus to Apecholinus Bernhauer, 1933 (comb.nov.), and Agelosus ohkurai and Agelosus pterosematicus are placed in synonymy with Apecholinus fraternus (syn.nov.). Staphylinus auroguttatus Cameron, 1932, Staphylinus bimaculatus Cameron, 1932 and Ocypus cameroni Smetana & Davies, 2000 (replacement name for bimaculatus Cameron, 1932) are transferred from Ocypus to Agelosus (comb.nov.) and placed in synonymy with Agelosus sikkimensis Bernhauer, 1920 (syn.nov.). Agelosus brevipennis Naomi, 1983, described as subspecies of Agelosus carinatus (Sharp, 1874), is placed in synonymy with Agelosus carinatus (syn.nov.). Agelosus chinensis J. Li, 1992 is transferred from Agelosus to Apecholinus Bernhauer, 1933 (comb.nov.) and placed in synonymy with Apecholinus fraternus (syn.nov.). Agelosus fushunicus J. Li, 2015 is placed in synonymy with Ocypus coreanus J. Müller, 1925 (syn.nov.). Agelosus unicolor masaoi Hyashi, 1991 is elevated to species rank (stat.nov,). Lectotype is designated for Ocypus weisei Harold, 1877.